Effect of acute feedback on knee angle and movements during a horizontal land and cut maneuver - Jensen, R.; Leissring, S.; Stephenson, M.; Wolfe, A.; Bellovary, B.; Glendenning, C.; Purdy, E.; Hagner, B.; Petushek, E. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to assess the effect of acute feedback and preferred plant leg on peak knee flexion and valgus angle, ground reaction force (GRF), and abduction moment of the knee during a horizontal land and cut maneuver. Eight division II women soccer players randomly performed horizontal landing and cutting maneuvers: 3 left and 3 right cuts pre- and post-feedback. Feedback was provided according to previous research. ANOVA revealed lower knee valgus angles for the feedback and preferred plant leg conditions (p<0.05). Knee flexion angle was greater when cutting on the preferred plant leg, but did not differ pre- or post-feedback (p >0.05). There were no differences in GRF or knee abduction moment. Acute feedback may decrease knee valgus angle during cutting tasks, but does not appear to acutely alter other measures that are thought to decrease ACL injury risk.